Feed Assessment Tool (FEAST) data repository - PHP code and database structure for website version 2.0.0 - Alemu, Miheretab; Mungai, Kevin; Fraval, Simon (International Livestock Research Institute, 2021)
This repository hosts version 2.0.0 of the PHP code and database structure for the FEAST Global Data Repository. Improvements in this version include a refreshed homepage, spatial data entry and download, new administrator functions, allowing data revisions while leaving raw data untouched, and modernizing the codebase for PHP 7.2.